The Levitating Firm. - KOPPL, ROGER (Independent Review)
The article discusses the concept of "levitating firms," which refers to corporations that own shares in one another, creating a network that diminishes market discipline and allows management to operate without accountability to shareholders. This phenomenon, termed "concatenated ownership," leads to a separation of ownership from control, enabling corporate management to prioritize their interests over those of shareholders, contrary to the principles of shareholder capitalism. The author argues that this structure undermines consumer sovereignty and promotes stakeholder capitalism, which is portrayed as a misguided response to the perceived shortcomings of shareholder capitalism. The article critiques the ideological shift towards stakeholder capitalism, suggesting it serves managerial interests rather than maximizing shareholder wealth, and calls for reforms to address the issues stemming from corporate self-ownership.